In silico Design of Novel HIV-1 NNRTIs Based on Combined Modeling Studies of Dihydrofuro[3,4-d]pyrimidines - Chen, Yanming; Tian, Yafeng; Gao, Ya; Wu, Fengshou; Luo, Xiaogang; Ju, Xiulian; Liu, Genyan (Frontiers in Chemistry, 2020)
A novel series of dihydrofuro[3,4-d]pyrimidine (DHPY) analogs have recently been recognized as promising HIV-1 non-nucleoside reverse transcriptase (RT) inhibitors (NNRTIs) with potent antiviral activity. To better understand the pharmacological essentiality of these DHPYs and design novel NNRTI leads, in this work, a systematic in silico study was performed on 52 DHPYs using three-dimensional quantitative structure–activity relationship (3D-QSAR), molecular docking, virtual screening, absorption-distribution-metabolism-excretion (ADME) prediction, and molecular dynamics (MD) methods. The generated 3D-QSAR models exhibited satisfactory parameters of internal validation and well-externally predictive capacity, for instance, the q2, R2, and rpred2 of the optimal comparative molecular similarity indices analysis model were 0.647, 0.970, and 0.751, respectively. The docking results indicated that residues Lys101, Tyr181, Tyr188, Trp229, and Phe227 played important roles for the DHPY binding. Nine lead compounds were obtained by the virtual screening based on the docking and pharmacophore model, and three new compounds with higher docking scores and better ADME properties were subsequently designed based on the screening and 3D-QSAR results. The MD simulation studies further demonstrated that the newly designed compounds could stably bind with the HIV-1 RT. These hit compounds were supposed to be novel potential anti-HIV-1 inhibitors, and these findings could provide significant information for designing and developing novel HIV-1 NNRTIs.